2005
DOI: 10.1002/pola.21095
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sequence‐controlled copolymers from extremely polar and apolar monomers by living radical polymerization and their phase‐separated structures

Abstract: A series of copolymers composed of two monomer units having a polar phosphorylcholine group and an apolar fluorocarbon group with a controlled monomer unit sequence were synthesized by a reversible addition‐fragmentation chain transfer (RAFT) living radical polymerization method. 2‐Methacryloyloxyethyl phosphorylcholine (MPC) and 2,2,2‐trifluoroethyl methacrylate (TFEMA) were selected as the monomers, because they have disparate polarity. Furthermore, to investigate the influence of the monomer unit sequence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…. [125] EtOEA [264] -C(Me)(CN)CH 2 CH(Me) 2 MMA [124] -C(Me)(CN)CH 2 CH 2 CO 2 H MAA a) [109] MMA [67,339] a) [109,143] b) [208] tBMA [153] DMAEMA [72,110,145,166] MAPS [160] DMAPS [169] c) [170] MAEHDMAB a) [143] MEPC [149,156] TFEMA [156] GluMA [172,173] MGluMA [173,174] Macro-MA a) [109] PEG-MA [100,160] MAm [178] DMAPMAm [179] HPMAm [180] MSASP [160] Sty [67,153,208] StySO 3 Na [67,72,110,235,236] StyCH 2 NH-(Me) 2 Cl [239] StyCH 2 N(Me) 3 Cl [235,236,239] DMHVBAC a) [143] DMVBAPS [169] BA a) …”
Section: Copolymerizationmentioning
confidence: 99%
“…. [125] EtOEA [264] -C(Me)(CN)CH 2 CH(Me) 2 MMA [124] -C(Me)(CN)CH 2 CH 2 CO 2 H MAA a) [109] MMA [67,339] a) [109,143] b) [208] tBMA [153] DMAEMA [72,110,145,166] MAPS [160] DMAPS [169] c) [170] MAEHDMAB a) [143] MEPC [149,156] TFEMA [156] GluMA [172,173] MGluMA [173,174] Macro-MA a) [109] PEG-MA [100,160] MAm [178] DMAPMAm [179] HPMAm [180] MSASP [160] Sty [67,153,208] StySO 3 Na [67,72,110,235,236] StyCH 2 NH-(Me) 2 Cl [239] StyCH 2 N(Me) 3 Cl [235,236,239] DMHVBAC a) [143] DMVBAPS [169] BA a) …”
Section: Copolymerizationmentioning
confidence: 99%
“…Gradient copolymers are of great interest because of their fascinating properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and their simple synthesis via controlled/living radical polymerization (CRP) techniques, 15 such as atom-transfer radical polymerization (ATRP), 2,[16][17][18][19] reversible addition-fragmentation transfer (RAFT), 20,21 and nitroxide-mediated CRP. 4,6,[8][9][10][11][12][13][22][23][24] Gradient copolymers have also been synthesized using other living or pseudo-living polymerization methods such as ring-opening metathesis polymerization 7,14,25 and cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the abnormally high water sorption of the fluorinated resin was probably due to the initiator, TBBO. It has been reported that the block copolymer of TFEMA with a hydrophilic monomer exhibits a phase-separated structure because of the extreme difference in their polarity 27) . In TFEMA-PTFEMA/TBBO resin, the concentration of TBBO in the TFEMA monomer liquid was relatively high, 8 wt%, and TBBO is known to exhibit a hydrophilic nature in polymerization reactions 28) .…”
Section: Discussionmentioning
confidence: 99%